Runoff responses to Atlantic multidecadal and Pacific decadal oscillations in China: Insights from the last millennium simulations - Yangyi Liu; Jie Chen; Lihua Xiong; Chong-Yu Xu (Journal of Hydrology: Regional Studies)
Study region: China Study focus: There is usually a teleconnection between large-scale climate indices and runoff. Among multiple large-scale climate indices, Atlantic Multidecadal Oscillation (AMO) and Pacific Decadal Oscillation (PDO) have received increased attention due to their long periodicities and low-frequency variability. However, the short observations limit the study of runoff response to AMO and PDO. Taking Medieval Climate Anomaly (MCA) and Little Ice Age (LIA) as study periods and focusing on summer runoff in China, this study aims to investigate 1) the major time scales at which AMO/PDO affects runoff, and 2) the individual and coupled effects of AMO and PDO on runoff by using last millennium climate model simulations. New hydrological insights for the region: AMO and PDO have stronger correlations with summer runoff at interdecadal time scales than at interannual time scales during MCA and LIA. For individual effects during MCA, the positive AMO phase can cause positive summer runoff anomalies in eastern China, northern China, and southern Qinghai-Tibet Plateau, while PDO has the opposite effect. The results during LIA are similar to those during MCA. For coupled effects during MCA, when the AMO phase is positive, the influence of PDO on runoff is much smaller than AMO. During LIA, the synergistic effects on summer runoff are shown by the in-phase AMO and PDO in southern China and the southern Qinghai-Tibet Plateau.